Shallow Water Equations in Hydraulics: Modeling, Numerics and Applications - Delis, Anargiros I.; Nikolos, Ioannis K. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue aims to provide a forum for the latest advances in hydraulic modeling based on the use of shallow water and related models as well as their novel application in practical engineering. Original contributions, including those in but not limited to the following areas, will be considered for publication: new conceptual models and applications, flood inundation and routing, sediment transport and morphodynamic modelling, pollutant transport in water, irrigation and drainage modeling, numerical simulation in hydraulics, novel numerical methods for the shallow water equations and extended models, case studies, and high-performance computing.